Young people's agency over continuing education in situations of early job insecurity: from enabling to stumbling. Issue 3 (1st September 2020) - Ilieva-Trichkova, Petya; Boyadjieva, Pepka
ABSTRACT: This article aims to explore how the situation of unemployment and – more generally – early job insecurity affects young people's scope for exercising agency with regard to decisions about continuing and improving their education. Drawing on the theoretical underpinnings of the capability approach, the article develops the concept of patterns of agency regarding continuing education. This concept refers to the mediating processes (interactions with others) whereby young people may convert available resources into new prospects for strengthening their capability to attain education as well as broadening their real choices with regard to education. Relying on information from a wide range of life-course interviews with young people born between 1990 and 1995 from seven European countries (Bulgaria, the Czech Republic, Germany, Greece, Norway, Poland and the United Kingdom), the present study applies the concept of patterns of agency regarding continuing education to the case of young people who have experienced early job insecurity. The analysis reveals the existence of two broad groupings of agency: enabled agency (patterns of realised interactions with institutions and individuals) and stumbled agency (patterns of non-realised interactions with institutions and individuals). The elaborated patterns provide a basis for fruitful future comparative analyses from different perspectives.